South Asian security and international nuclear order [ creating a robust Indo-Pakistani nuclear arms control regime - Carranza, Mario Esteban (Farnham, England;Burlington, Vermont : Ashgate Publishing, 2009)
Mario Carranza studies in depth the linkages between Indo-Pakistani nuclear relations and the International Nuclear Order. He critically analyzes the de facto recognition by the United States of India and Pakistan as nuclear weapon states and looks at the impact of that recognition on the International Nuclear Order and its linchpin, the Nuclear Non-Proliferation Treaty (NPT). The book provides a critical analysis of the New International Nuclear Order sponsored by the United States after the September 11 terrorist attacks and the place of India and Pakistan in that order. The author considers the survival of India and Pakistan in relation to a strategy of nuclear deterrence and debates the possibility of establishing a robust nuclear arms control regime in South Asia as part of a broader effort to revive global nuclear arms control and disarmament negotiations
1. Introduction: Indo-Pakistani nuclear relations and the crisis of the international nuclear order --2. Dangerous optimism: Indo-Pakistani nuclear relations before the May 1998 nuclear tests --3. South Asian security after the Indian and Pakistani nuclear tests --4. India-Pakistan crises after the nuclear tests: the Kargil war (1999) and the 2001-2002 border confrontation --5. US policy toward South Asia: from non-proliferation to post-proliferation and the US-India nuclear deal -- 6. Conclusion: South Asian security and the post 9/11 international nuclear order: can the genie be put back in the bottle?
Description based on print version record
Includes bibliographical references and index
Keywords: Non-Proliferation Treaty Review Conference; Nuclear arms control -- India; Nuclear arms control -- Pakistan; Nuclear nonproliferation -- India; Nuclear nonproliferation -- Pakistan; Security, International -- India; Security, International -- Pakistan; Nuclear arms control; India -- Foreign relations -- Pakistan; Pakistan -- Foreign relations -- India